TEACHERS' WELFARE AND STUDENTS' ACADEMIC ACHIEVEMENT IN SCIENCE IN BORNO STATE COLLEGES OF EDUCATION - Muhammed, Abubakar Siddiq; Dapshima, Grema Ali (Sokoto Educational Review, 2017)
The main purpose of the study was to examine welfare of teachers and students ’ academic achievement in Borno State Colleges of Education. A research question and mill hypothesis were tested. A survey research design was employed for the study, covering an accessible population of 487 academic staff. The sample size of the study Was 195 academic staff, using simple random sampling 40% Of the population as the sample size for the study. These are dcadeniiC staff from three Colleges of Education with sample size of 67, 76 and 52 respectively. Also results of students’ academic achievement for the period of five years (2004/2005 - 2008/2009 academic sessions) was used in five courses; Biology, Chemistry, Mathematics, Physics and Integrated Science. The data collected through questionnaire and documentary evidence of results Were analyzed using mean, standard deviation and Pearson correlation. The Reliability coefficient of the instrument was established as 0.92 and this was considered High enough to accept the homogeneity of the instrument. The study revealed that there was fairly adequate provision Of teachers’ welfare in the colleges and there is significant relationship (at 0.05 level) between welfare of teachers and students’ academic achievement. Based oil these findings, it is recommended, among others, that Borno state Government should improve is provision of teachers ’ Welfare in these colleges of education.